NRLMSIS 2.0: A Whole‐Atmosphere Empirical Model of Temperature and Neutral Species Densities. Issue 3 (17th March 2021) - Emmert, J. T.; Drob, D. P.; Picone, J. M.; Siskind, D. E.; Jones, M.; Mlynczak, M. G.; Bernath, P. F.; Chu, X.; Doornbos, E.; Funke, B.; Goncharenko, L. P.; Hervig, M. E.; et al.
Abstract: NRLMSIS® 2.0 is an empirical atmospheric model that extends from the ground to the exobase and describes the average observed behavior of temperature, eight species densities, and mass density via a parametric analytic formulation. The model inputs are location, day of year, time of day, solar activity, and geomagnetic activity. NRLMSIS 2.0 is a major, reformulated upgrade of the previous version, NRLMSISE‐00. The model now couples thermospheric species densities to the entire column, via an effective mass profile that transitions each species from the fully mixed region below ~70 km altitude to the diffusively separated region above ~200 km. Other changes include the extension of atomic oxygen down to 50 km and the use of geopotential height as the internal vertical coordinate. We assimilated extensive new lower and middle atmosphere temperature, O, and H data, along with global average thermospheric mass density derived from satellite orbits, and we validated the model against independent samples of these data. In the mesosphere and below, residual biases and standard deviations are considerably lower than NRLMSISE‐00. The new model is warmer in the upper troposphere and cooler in the stratosphere and mesosphere. In the thermosphere, N2 and O densities are lower in NRLMSIS 2.0; otherwise, the NRLMSISE‐00 thermosphere is largely retained. Future advances in thermospheric specification will likely require new in situ mass spectrometer measurements, new techniques for species density measurement between 100 and 200 km, and the reconciliation of systematic biases among thermospheric temperature and composition data sets, including biases attributable to long‐term changes. Key Points: A major, reformulated upgrade to NRLMSISE‐00 is presented using extensive new data sets from the ground to ~100 km altitude Vertical structure of the atmosphere is now self‐consistently coupled; O density now extends down to 50 km New model is warmer in upper troposphere, cooler in stratosphere and mesosphere; thermospheric N2 and O densities are lower